A comparative study of dried apple using hot air, intermittent and continuous microwave: evaluation of kinetic parameters and physicochemical quality attributes. Issue 6 (11th May 2015) - Aghilinategh, Nahid; Rafiee, Shahin; Gholikhani, Abolfazl; Hosseinpur, Soleiman; Omid, Mahmoud; Mohtasebi, Seyed S.; Maleki, Neda
Abstract: In the study, the effectiveness of intermittent (IMWD) and continuous (CMWD) microwave drying and hot air drying (HAD) treatments on apple slices were compared in terms of drying kinetics (moisture diffusivity and activation energy) and critical physicochemical quality attributes (color change, rehydration ratio, bulk density, and total phenol content (TPC) of the final dried product. The temperature, microwave power, air velocity, and pulse ratio (PR) applied in the experiments were 40–80°C, 200–600 W, 0.5–2 m/s, and 2–6, respectively. Results showed that IMWD and CMWD more effective than HAD in kinetic parameters and physicochemical quality attributes. Also, results indicated CMWD had the lowest and highest drying time and effective diffusivity. The exponential model for estimating IMWD activation energy, considering absolute power (1/P) and pulse ratio were also represented. The color change in apple slices dried by HAD showed the highest change. Abstract : Continuous microwave drying (CMWD) rendered the lowest color change and the highest TPC, while IMWD had the lowest and highest bulk density and rehydration ratio. Therefore, CMWD is recommended for the drying of apple slices when the TPC and the amount of color change are at stake.